Internal Service Quality as a Driver of Employee Satisfaction, Commitment, and Turnover Intention Exploring over focal role of Employee Well-Being - Safara Putri Maharani; Tantri Yanuar Rahmat Syah; Dimas Angga Negoro (Journal of Multidisciplinary Academic, 2020)
The purpose of this study aimed to use paradigms to introduce “employee well-being” as a focal construct in the process by which internal service quality (ISQ) drives employee satisfaction, commitment and turnover intention. In this study, we use SEM analysis (Structural Equation Model) over 125 correspondents with filled a questionnaire. The scale carried out in this study uses a Likert scale consisting of a scale of one to five. The results of the study were ISQ has a positive effect on employee satisfaction & employee well-being in airlines company. This study is uses data from a single company in Tangerang, Indonesia and focuses on a few key constructs, which is restrict the generalizability of its findings. Moreover, no significant differences were found among the workers units.